2016
DOI: 10.1017/s1751731116000847
|View full text |Cite
|
Sign up to set email alerts
|

Pigs that are divergent in feed efficiency, differ in intestinal enzyme and nutrient transporter gene expression, nutrient digestibility and microbial activity

Abstract: Feed efficiency is an important trait in the future sustainability of pig production, however, the mechanisms involved are not fully elucidated. The objective of this study was to examine nutrient digestibility, organ weights, select bacterial populations, volatile fatty acids (VFA's), enzyme and intestinal nutrient transporter gene expression in a pig population divergent in feed efficiency. Male pigs (n = 75; initial BW 22.4 kg SEM 2.03 kg) were fed a standard finishing diet for 43 days before slaughter to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
52
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 35 publications
8
52
4
Order By: Relevance
“…In the present study, however, we did not observe differences in the jejunal expression of nutrient transporters SGLT1 and MCT1 between RFI groups. In considering that Vigors et al [3] sampled the proximal jejunum (60 cm from the stomach), whereas in the present study we collected mucosal samples from the distal part of the jejunum, this may explain the contrasting observations between the previous and the present study.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In the present study, however, we did not observe differences in the jejunal expression of nutrient transporters SGLT1 and MCT1 between RFI groups. In considering that Vigors et al [3] sampled the proximal jejunum (60 cm from the stomach), whereas in the present study we collected mucosal samples from the distal part of the jejunum, this may explain the contrasting observations between the previous and the present study.…”
Section: Discussionmentioning
confidence: 56%
“…In fact, we found a greater activity of maltase, sucrase and lactase at the duodenal brush border in low RFI pigs than in high RFI pigs but only in those from AT, although pigs from all locations were in the early postprandial state at slaughter. Vigors et al [3] also observed a greater expression of sugar transporters SGLT1 , GLUT2 and fatty acid transporter FABP2 in the jejunum together with an enhanced apparent total tract digestibility of dry matter, nitrogen and gross energy in low versus high RFI pigs. In the present study, however, we did not observe differences in the jejunal expression of nutrient transporters SGLT1 and MCT1 between RFI groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It demonstrated an increased abundance of Lactobacillus in the cecum of more feed-efficient pigs; however, only Firmicutes, Bacteroidetes, Bacteroides, Lactobacillus, and Enterobacteriaceae were measured (by quantitative PCR). Pigs with better FE also tended to have higher concentrations of total VFAs in the cecum and butyric acid in the colon, which may be explained by differences in microbial composition and function (14,23).…”
mentioning
confidence: 99%